2022
DOI: 10.1007/s12144-022-02831-7
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory volunteers’ nostalgia and its relationships with positive memories, age, past experiences, and volunteer intention

Abstract: While nostalgia has been explored in various contexts, no research has so far investigated how individuals’ nostalgia can be generated by volunteer experiences in compulsory settings and how nostalgic feelings extend their future behavior. To fill this research gap, this study explored how nostalgia regarding compulsory volunteering is related to positive memories, age, and past experiences and how such nostalgia translates to volunteer intention. A total of 605 responses were collected from university student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Intention to continue volunteering was measured using three items adapted from Hoye et al (2008). The scales used in this study showed reliability and validity in previous research (e.g., Crawford and Henry, 2004;Park and John, 2012;Cho and Joo, 2022), and the items are in the form of 7-point Likert scales, where participants indicate their level of agreement from (1) strongly disagree to (7) strongly agree. The wording of these items is listed in Table 1, and psychometric properties are reported in Table 2.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Intention to continue volunteering was measured using three items adapted from Hoye et al (2008). The scales used in this study showed reliability and validity in previous research (e.g., Crawford and Henry, 2004;Park and John, 2012;Cho and Joo, 2022), and the items are in the form of 7-point Likert scales, where participants indicate their level of agreement from (1) strongly disagree to (7) strongly agree. The wording of these items is listed in Table 1, and psychometric properties are reported in Table 2.…”
Section: Methodsmentioning
confidence: 79%
“…Additionally, in an occupational setting, Staw et al (1994) noted that employees who experienced positive emotions at work were more likely to engage in favorable work behaviors, allowing them to achieve their goals. More relevant to the present study's context, Aknin et al (2018) and Cho and Joo (2022) stressed that positive emotions from prosocial behaviors act as reinforcement and encourage individuals to continue engaging in prosocial behavior. Therefore, this study hypothesized that the intention to continue volunteering, a type of prosocial behavior, is influenced by the experience of positive emotions: H6: Volunteers' positive emotions positively affect intention to continue volunteering.…”
Section: Continuance Intentionmentioning
confidence: 92%